Modeling of sago starch hydrolysis using glucoamylase - Long, Wee Lai; Faizal Yahaya; Mohamad Suffian Mohamad Annuar (Universiti Kebangsaan Malaysia, 2015)
A mathematical model based on Michaelis-Menten kinetics was proposed and used to simulate the sago starch hydrolysis and the remaining sago starch concentration. The simulation model was tested with comparison to the real experimental results. The glucoamylase enzyme (E.C. 3.2.1.3) from Aspergillus niger was employed in the present study to hydrolyze the substrate i.e. sago starch into reducing sugars. The experiment was performed in a 2 L stirred tank reactor. The quantitative effects such as temperature, substrate concentration, enzyme amount, pH and agitation speed were set to optimal value at 61°C, 1.0 gL–1, 0.2 Uml–1, pH4.5 and 100 rpm, respectively. The computer software, Polymath® 6.0 was employed in this research. The numerical method based on Runge-Kutta Fehlberg 45 was used to solve the system of non-linear ordinary differential equations (ODEs) of sago starch hydrolysis. The model prediction was well agreed with experimental results where the high values of regression coefficient, R2 = 0.9643 was obtained.